Pengaruh Penempatan Penghalang Berbentuk Silinder Pada Posisi Vertikal Dengan Variasi Jarak Horisontal Di Depan Silinder Utama Terhadap Koefisien Drag - Gunawan Tista, Si Putu Gede (Jurnal Energi Dan Manufaktur; Vol 4, No.2 Oktober 2010)
One of the ways to reduce energy consumption on the air plane and the other bluff bodies are by decreasing the drag. Dragis closely related to the flow separation. The earlier separation, then the drag will increase more. Based of the fact the effortto decrease drag is conducted by manipulating the field of fluid flow. Stream manipulation was be done by installingcylindrical obstacle in front of main cylinder. The purpose of this research is to analyze the effect of placement cylindricalobstacle at vertical position in the various horizontal distance in front of main cylinder on drag coefficient . In thisresearch, the experiment was conducted in the wind tunnel, which consisted of blower, pitot pipe, manometer, cylinder pipe,and cylinder rod. The cylindrical obstacle was positioned at vertical (y=14 mm) in the various horizontal distanceL/D = 1.41, L/D = 1.56, L/D = 1.72, L/D = 1.88, L/D = 2.03, L/D = 2.19, and L/D = 2.81 by upstream from the maincylinder. Diameter cylinder obstacle was 8 mm.. The Reynolds number based on the main cylinder diameter (D = 42 mm)was Re = 3.42 x 104. The research results showed that the cylinder rod could decrease the drag coefficient of main cylinder.Drag coefficient for cylinder without cylinder rod was 0.167 while the biggest decrease of coefficient of drag with cylindricalobstacle was happened at L/D = 1.72 which was 0,0593. It means that the drag coefficient of main cylinder with cylindricalobstacle was 64.5% lower than the cylinder alone.
Keywords: cylinder obstacle, Position and distance obstacle, Separation, Drag Reduction.